Studi Kadar Nikotin dan Tar Sembilan Merk Rokok Kretek Filter yang Beredar di Wilayah Kabupaten Nganjuk - Kusuma, Dani Ali; Yuwono, Sudarminto S.; Wulan, Siti Narsito (Jurnal Teknologi Pertanian, 2004)
Tar and nicotine are subtances contained in cigaretes. Nicotine is adictive, while tar is carcinogenic and causing some diseases. Aim of this research was to know the tar and nicotine content of kretek filter cigaretes sold in Nganjuk district. Multiple sampling method was used to collect data. The data obtained were analyzed using Randomized Block Design. Results showed that nicotine content range from 1,10-2,17% and 2 brands contained nicotine more than the standard (maximum 2,0%). The tar content ranged from 0,05-0,175% and all brands contained the tar under the standard (1,5%). Â  Key words : Kretek filter cigaretes, tar, nicotine